Perbandingan Pengaturan Hukuman Mati di Indonesia dan Amerika Serikat - Widyaningrum, Hesti (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2020)
This article discuss the comparison of the death penalty between Indonesia and the United States which has a different legal system. This study used normative juridical method by comparing the legal system and the implementation of death penalty in the two countries. The difference of the death penalty in Indonesia and the United States lies in the crime. In America, life-threatening, cruel crimes and genocide are regulated in the United States Code. Whereas in Indonesia, Criminal death for genocide, foreign smuggling crimes, and drug crimes are enforced in the Special Act where the crime is included in the category of special crimes. Alternative punishment for death penalty also differs between Indonesia and America where the fine is a cumulative or facultative crime with a specific imprisonment as an alternative punishment for death peanlty. The conclusion of this study shows that the application of death peanlty is not based on the legal system adopted by a country both in the common law and civil law. Criminal Code in Indonesia does not always contain acts of crime that are punishable by death, while in USC in America contains criminal acts pusisable by death.